Through a lens of affect: multiliteracies, English learners, and resistance. Issue 5 (2nd September 2020) - Burgess, Julianne
ABSTRACT: This autoethnographic study explores disruptive moments in a multiliteracies English-as-an-Additional Language (EAL) classroom with young adult students. Using a lens of affect theory, the study presents three strategic sketches (vignettes) to shine a light on unexpected intensities in the learning assemblage, initially assumed to be learner ambivalence, uneven investment and resistance, to multiliteracies pedagogy. Through autoethnographic inquiry, a writing of the self, this paper argues that affectively charged moments in literacy and language setting should be recognized as Deleuzian sense-events that are resistant to interpretation. The possibilities created by learning and teaching through sense-events and sensational pedagogies offer alternatives for doing multiliteracies and challenge the foundations of English language teaching, by proposing other ways of articulating meanings and experiences outside of language.